The Romantic Fragment as a Key to a New Reading of Song of Songs - Naishṭaṭ Bornshṭein, Lilakh (Hebrew studies, 2020)
The secret of Shir Hashirim—the Song of Solomon—defies decryption. Few commentators dare to acknowledge the incomprehensibility of Song of Songs, yet the many interpretations that attempt to cope with the poem fail to tackle the problems of lack of context, disintegration, and fluid boundaries between literal and metaphoric meanings. Here, however, these predicaments are represented not only as bumps on the road to an integrative interpretation of the Song but also, and mainly, as the epitomic characteristics of Song of Songs, via direct reference to the Romantic Fragment genre., That Song of Songs may be set within the context of the Romantic Fragment is not self-evident. This poem has never been read this way even though it is characterized as such at several levels. The reading dynamic in this poem is typified by a fascinating interplay of integration versus disintegration, disconnection between textual segments and the world, and redundancy coupled with information gaps. The readers face fluidity of borders between concrete and metaphoric meanings, between innocent and sinful, what is seen and what is heard, and among real world and dream world., A close examination shows that Song of Songs is characterized by disintegration and multiple frameworks that switch off between rivalry and contradiction. Below the links and tensions in Song of Songs are described within a perspective frame. By combining the historical point of departure with theoretical tools, it becomes possible to surmount the narrow characteristics of the Romantic Fragment in order to portray traits of the Fragment as a historical genre and, concurrently, to derive a theoretical model of the reading process.